Editorial. Sport in the Context of Migration and Health Crises - Bortoletto, Nico; Michelini, Enrico; Porrovecchio, Alessandro (Italian Sociological Review, 2021)
Recent crises, from the economic and migratory to the recent COVID-19 pandemic, have dramatically affected all areas of individual and collective life – and sport and physical activity are no exception. The main aim of this special issue is to bring researchers interested in sports and physical activity to propose their works. The focus of this special issue lays in the new challenges that sociology of sports and physical activity have to face to understand these new complex scenarios, the main issues we had to face, the successes, the criticalities and the lessons learned.